UPAYA PENINGKATAN PEMAHAMAN KONSEP FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER - Indra Swastika Triutama; Dasmo Dasmo; Dandan Luhur Saraswati (UNIVERSITAS INDRAPRASTA PGRI, 2023)
This study aims to determine the effect of the Numbered Heads Together (NHT) type of cooperative learning model on the understanding of the physics concept of class VIII students of SMP Islam Ibnu Majah Bording School Bekasi. Based on the results of data analysis, it is known that the sample class is normally distributed and has a homogeneous variance. The results of the hypothesis test were obtained using the one-sided t test with a t_count value = 6.33 and a large t_table value at a significant level of Î± = 0.05 and degrees of freedom (dk) = 38, the value of t_table = 1.69 was obtained. So that the data obtained t_count>t_table = 6.33 > 1.69, it can be concluded that the NHT type cooperative learning model can increase students' understanding of physics concepts in class VIII Islamic Middle School Ibnu Majah Boarding School Bekasi.